MiR-22 protect PC12 from ischemia/reperfusion-induced injury by targeting p53 upregulated modulator of apoptosis (PUMA). Issue 1 (1st January 2020) - Jiao, Hongmei; Chen, Renyi; Jiang, Ziru; Zhang, Lin; Wang, Hongwei
ABSTRACT: MicroRNAs have been implicated as critical regulatory molecules in many cerebrovascular diseases. Recent studies demonstrated miR-22 might provide a potential neuroprotective effect. However, the neuroprotective effect of miR-22 in ischemia/reperfusion (I/R) injury has not been thoroughly elucidated. In this study, the PC12 cells were subjected to 4 h oxygen and glucose deprivation (I) and 24 h reoxygenation (R). The PC12 cells were pre-transfected with miR-22 or anti-miR-22 or siRNA-mediated downregulation of p53-upregulated-modulator-of-apoptosis (PUMA)(PUMA siRNA) or their controls at 24 h prior to exposure to I/R. Reverse transcription-quantitative polymerase chain reaction (RT-qPCR) and Western blot were employed to analyze mRNA and protein expression. PI and Annexin V assays and terminal deoxynucleotidyltransferase-mediated dUTP-biotin nick end labeling (TUNEL) assay were used to quantify the rate of apoptosis. We found that miR-22 expression was significantly downregulated in the PC12 cells subjected to I/R. Loss of function of miR-22 increased PC12 apoptosis after I/R, and overexpression of miR-22 decreases PC12 apoptosis after I/R. PUMA protein was upregulated in the I/R group as compared with the sham group. The increased PUMA protein expression and apoptosis induced by I/R was reversed by transfection with PUMA siRNA. We concluded that I/R enhanced apoptosis and PUMA expression in PC12 cells via downregulation of miR-22. Enhanced miR-22 expression reversed both PUMA expression and apoptosis induced by I/R in PC12 cells. miR-22/PUMA axis has important implications for their clinical applications. Graphical Abstract: